Value Creation and Value Capture: Lessons Learnt from Indonesian Suppliers Inserted into GVC - Kadarusman, Yohanes Berenika (Jurnal Ekonomi Indonesia, 2020)
The development of global value chain (GVC) has confirmed a paradigm shift in international studies. GVC suggests that the globalization of economic activity brings about gains for developing countries through capability improvement of their firms supplying for lead firm. Nevertheless, there is only a small number of developing countries insert into GVC and successfully enhance their economy. This paper aims to understand how developing countries decide to participate in and to upgrade along GVC by taking cases from Indonesian suppliers across industries. The narratives reveal that the distribution of value creation between Indonesian suppliers and lead firm within GVC is critical for the decision making to engage and to upgrade. It indicates that the suppliers scrutinize the relationship to ensure that the value creation is not only technically feasible to fit intheir existing resources and capabilities, but more importantly economically justifiable to capture more of value being created. The problem of power asymmetry tends to result in inequitable distribution of cost and benefit in value capture by Indonesian suppliers and lead firm. This makes the value creation and value upgrading within GVC less economically attractive course of action. The implication for further research on GVC shouldhighlight the value capture particularly within governance in which power asymmetry exists, while public policy should facilitate to strengthen distinctive resources and capabilities of suppliers.